Detection of leptospiral DNA in urine sample following prolonged hospitalization: a case report - Othman, Shuhaidah; Philip, Noraini; Mohd Taib, Niazlin; Neela, Vasantha Kumari; Chee, Hui Yee (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
We described a case of positive molecular detection of leptospirosis in urine sample following prolonged hospitalization. Relevant clinical history had raised suspicion to leptospirosis infection. A significantly high level of creatinine kinase suggested possibility of rhabdomyolysis. Blood and urine samples collected on 4th day of admission were negative for leptospires culture and serological method showed no significant evidences of positive infection. Molecular detection of Leptospira spp. in blood sample was positive but not in urine sample. After seven weeks of infection, leptospiral DNA was detected in urine sample using molecular method.